TATANIAGA BUNGA MELATI DI DESA LABUAN TABU, KECAMATAN MARTAPURA, KABUPATEN BANJAR - E. Hardiati; S. Suwasono (BUANA SAINS, 2006)
A study that was aimed to analyze margin and efficiency of jasmine marketing had been conducted at Labuan Village, Martapura district of Banjar Regency. The study objects covered farmers, traders, and consumers. Qualitative analyses were performed to describe marketing channels, marketing functions, and related agencies. Quantitative analyses were used to calculate marketing margin. Results of this study showed that there had been four channels of jasmine marketing. Marketing functions that were performed by marketing agencies included trading, physical and facility functions. The highest profit made was found at channel three. The most efficient marketing process was observed at channel one (farmers-consumers)